"And We Shall See Him Face to Face": A Trinitarian Analysis of the Beatific Vision. (December 2021) - Ormerod, Neil
A traditional account of the beatific vision has focused attention on our vision of the divine essence. However, little attention has been paid to the trinitarian aspects of the vision. This article proposes a trinitarian account of the beatific vision drawing on the work of Bernard Lonergan and Robert Doran and the so-called four-point hypothesis. It concludes that, so conceived, the beatific vision is analogous to an exchange of wedding vows.